“Seleccion participativa de variedades locales promisorias de (coffea arabica) en productividad y tolerancia a roya (Hemileia vastatrix) en la región San Martín” - Vasquez Tenazoa, Antony (2015)
This research entitled "Participatory variety selection of local promising of Coffea arabica in productivity and tolerance to roya (Hemileia vastatrix) in San Martin region" had as development sites four provinces (Lamas, El Dorado, Huallaga and Rioja). In arder to conduct a participatory selection via surveys to coffee farmers, considering the health status of agricultura! practices that take place on their land determining four variety (yellow caturra, pache, catuai and national). This study included an analysis of the quantitative variables in the four provinces of a completely randomized design 4x2 with two components under study: altitude and variety: Altitude includes two levels of 800-1000 and 1000-1200 meters above sea level. Varieties include the following: pache, national, red and yellow caturra; each province had an evaluation according to the criteria and scales in the methodology of this study. The dependent variables analyzed are fruit size, number of internodes, roya tolerance. Keywords: Roya tolerance, productivity, altitude.